Locutionary, Illocutionary and Perlocutionary Acts in the Short Story â€œLetters from the Fatherâ€ by Mona Trisyah - Aulia Fitriyani; Intan Sari Ramdhani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Speech acts are not only found in oral communication, but also in written form as in prose-shaped literary works, one of which is short stories. The structure of language and the structure of society influence each other. The emergence of linguistic units cannot be explained only by linguistic rules. There is a phenomenon which shows that one utterance can be used to express various kinds of speech acts. This research is a qualitative descriptive study. The description of the data is in the form of story excerpts and dialogue in the short story "Letter from Father" by Mona Trisyah which contains locutionary, illocutionary and perlocutionary speech acts using theoretical concepts related to this study. The data source used for this study is the short story "Letter from Father" by Mona Trisyah. The type of research data is written data, in the form of story quotes and dialogues in short stories that contain locutionary, illocutionary, and perlocutionary speech acts. This article aims to describe the types of locutionary acts, illocutionary acts, and perlocutionary acts in the short story "Letters from Father" by Mona Trisyah